Erratum: JI, D. et al. (2011) Redescriptions of five species of marine peritrichs, Zoothamnium plumula, Zoothamnium nii, Zoothamnium wang, Pseudovorticella bidulphiae, and Pseudovorticella marina (Protista, Ciliophora). Zootaxa, 2930, 47–59. - Ji, D. (Zootaxa, 2011)
(Erratum)